Kritik Nalar Tafsir Syi’ri - Aksin Wijaya (Millah: Journal of Religious Studies, 2010)
The article exposes the critique of Thoha Husein on the logical reasoning of syi’ri tafseer commonly used by several tafseer experts, such as al-Zarkasi, al-Suyuti, and al-Thabari. The logical reasoning of syi’ri tafseer developing until today states that Al-Qur’an was descended using Arabic language in which some of the verses refer to the Jahiliah syi’ir that existed in the Arab community at the time. Thoha Husein criticizes on the opinion. His argument is on the authenticity of jahiliyah syi’ir, not on the urgency of its usage to understand difficult words of Al-Qur’an. According to him, those are not really jahiliyah syi’ir, but they were made by plagiarists during Islamic era for hidden interest.